INJEKSI OODEV TERHADAP REMATURASI IKAN PAPUYU (Anabas testudineus, Bloch) DI DALAM WADAH BUDIDAYA - Iftisar Rozikin; Untung Bijaksana; Akhmad Murjani (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2019)
The Reproductive ability of parent fish which just finish spawming are common with stage I of gonadal maturity takes for a long time. Gonad may not mature if it is notgiven treatment. Doses of OODEV between 0,3 – 07 cc/kgs body weight give effect in inducing gonadal maturation.This Research shows that the highest fecundity was an average of 33190 eggs obtained from on Treatment C, and the largest egg diameter was an average of 0,7 mm also obtained in the treatment C. The highest HIS score was in treatment C (0,95%), while the highest IGS value obtained in treatment A (13,183%). The result of the Observations on the gonad histology climbing perch parent fish was the treatment with OODEV hormones caused the development of maturity level. Change in values and levelsof water quality were considered metting the standard for live fish climbing perch fish. The statistical test result on all the above test parameters showed that al was notsignificantly different among all treatment given; thus from the given hypothesis HO wasaccepted and H1 was rejected which means that OODEV injection dose did not significantly affect the maturation procces. The treatmen with OODEV was more than the level without the use of OODEV Hormones (Control). This is because of the role of the FSH in OODEV Hormone influenced the development of biosytesis of estradiol -17 betha and gonad.